A Retrospective on Teenage Pregnancy in Poland: Focussing on Empowerment and Support Variables to Challenge Stereotyping in the Context of Social Work. - Odrowąż-Coates, Anna; Kostrzewska, Dagmara (Child & Adolescent Social Work Journal, 2021)
The article focuses on selected predicators of successful and fulfilling teenage motherhood. It contains analysis of qualitative data, obtained through comprehensive interviews and field notes from social work practice, based on the personal experiences of teenage mothers and a court appointed family curator. Using herstory perspective, it aims to present positive examples of teenage motherhood as a source of empowerment and independence, to unveil and combat stereotypical views on adolescent mothers in Poland. Moreover, the authors discuss systemic issues and challenges as well as a social stigma created by public opinion and aim to challenge harmful stereotyping. The article contributes to social work practice for the purpose of enhancement of the international comparative studies in this field.